2021
DOI: 10.1080/12265934.2021.1915854
|View full text |Cite
|
Sign up to set email alerts
|

National borders transcended: the impact of geographical proximity on the growth of global innovation networks among cities in East Asia

Abstract: Recently, the concept of the global innovation network (GIN) has been emphasized in view of increasing joint international research within regional economies as enabled by drastic changes in technology. However, insights gained from quantitative analysis of GINs are lacking. This study empirically investigated the GINs among major cities in East Asia by using data on patented co-inventions. This included an analysis of the factors that influence networks in the formation of international research collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Similarly, a country’s location in a dense co-inventor network cluster may help increase its reputation and send a signal to inventors from countries outside the cluster to start collaborating with its inventors. For example, Lim and Han’s study [ 50 ], found that there was strong collaboration between inventors from countries in East Asia, which gave them important critical mass in the network of all inventors and made them attractive to other inventors from outside the regional cluster. Clustering has not yet been explored in depth at the regional level, but Turkina and Oreshkin [ 16 ] provide a city-level example of clustering at work.…”
Section: Co-inventor Network Effects On the Innovation Performance Of...mentioning
confidence: 99%
“…Similarly, a country’s location in a dense co-inventor network cluster may help increase its reputation and send a signal to inventors from countries outside the cluster to start collaborating with its inventors. For example, Lim and Han’s study [ 50 ], found that there was strong collaboration between inventors from countries in East Asia, which gave them important critical mass in the network of all inventors and made them attractive to other inventors from outside the regional cluster. Clustering has not yet been explored in depth at the regional level, but Turkina and Oreshkin [ 16 ] provide a city-level example of clustering at work.…”
Section: Co-inventor Network Effects On the Innovation Performance Of...mentioning
confidence: 99%
“…Empirical studies so far have typically employed concepts and techniques from spatial interaction theory to explore drivers for cross-region innovation networks, often in relation to the proximity concept (Boschma 2005). Here, special emphasis has been put on how different types of proximities -such as geographical proximity, but also technological, cultural, or institutional proximities -affect collaborations in innovation activities between actors located in different regions (e.g., Vieira et al 2022;Lim and Han 2023). While previous research also emphasizes the importance of network structural mechanisms that may be at stake in the formation and development of such networks, they stay rather vague in their empirical approach to identify such network structural mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, to further integrate into the GIN, China has launched a series of policies, including the ‘Special Plan for International Cooperation in Science and Technology Innovation’ during the 13th Five‐Year Plan period and the Special Plan for Science and Technology Innovation Cooperation included in the Belt and Road Initiative, to promote the formation of an international system of division of labor between industries and countries, ultimately forming a sustainable model of innovation and development. At present, innovation networks within the Belt and Road Initiative are beginning to exhibit regional clusters (Wang et al., 2017), increasing China's share in the innovation network of major regions in East Asia (Lim and Han, 2023). However, developed European and North American countries still dominate and control transnational patent coordination, and China has yet to demonstrate influence within GINs (Bai et al., 2022).…”
Section: Introductionmentioning
confidence: 99%